Images of the Indigenous Body in Latin America: Archives of Enemization (Andamios, Revista de Investigación Social, 2026)
The purpose of this article is to analyze the images that represent indigenous people in relevant historical works in Argentina, Colombia, Chile and Peru. It is not only about illustrations and the use of visual production techniques, but also about the production of an archive that is part of the visual culture of the society of the time. For this purpose, three interpretative schemes of the indigenous and three socio-cultural elements are considered: visuality, image and gaze. This work is characterized by the breadth and comparative character of the corpus analyzed, being its main findings the use of enemization strategies such as the control of emotions, especially behavior, manners and clothing; as well as the use of shame and the reification of the body of the other, imposing a mode of consciousness of the indigenous being.
Keywords: Indigenous body; archives; enemization; indigenous interpretative schemes; analysis of the images